Artists and Architecture. : Variable Dimensions. - Gourvennec Ogor, Didier; Albertazzi, Liliana; Benedetti, Lorenzo; Gadanho, Pedro; Zwingenberger, Jeanette (Paris : Editions du Pavillon de l'Arsenal, 2015)
Absalon, Acconci, Vito ; Afif, Saadane ; Aitken, Doug ; Kassen, A ; Albertazzi, Liliana ; Alüs, francis ; Anselmo, Giovanni ; Antunes, Leonor ; Aroujo, Juan ; Ardouvin, Pierre ; Armajani, Siah ; Arsham, Danie ; Atassi, Farah ; Aubry, Michel ; Baloji, Sammy ; Beer, Oliver ; Beloufa, Neil ; Biscotti, Rossella ; Dedobbeleer, Koenraad ; Fassler, Larissa ; Koelewijn, Job ; Bodys isek Kingelez ; Knowles, Alison ; Gaba, Meschac ; Goiris, Geert ; Gupta, Subodh ; Nkanga, Otobong ; Kwade, Alicja ; Raad, Walid ; Raissnia, Raha
Artistes et Architecture. Dimensions variables, oktober 2015, Pavillion de l'Arsenal
boek